Combined effect of various operating loads, number of feed water heaters and makeup water quantities on the performance of coal fired thermal power plant: A case study. Issue 1 (31st December 2016) - Geete, Ankur; Bhargava, Ajay
Abstract: In this case study, combined effect of various operating parameters on the performance of thermal power plant is analyzed. For the analysis following operating parameters are selected: different operating loads, different number of feed water heaters and different mass flow rates of makeup water. To analyze the performance of the power plant: flow function, mass flow rates of steam at each stage, power output, heat rate, correction factors for power and heat rate are evaluated. And then performance characteristic curves are prepared. Finally those operating conditions are found at which power output is as high as possible but heat rate is as low as possible. This case study can be concluded as maximum power (121.21 MW) and minimum heat rate (2, 393.05 kJ/MW s) both can be achieved at full operating load condition, with five feed water heaters and no makeup water addition in deaerator. But minimum power (71.43 MW) and maximum heat rate (2, 430.94 kJ/MW s) are found at low load, with large number of feed water heaters and more amount of makeup water addition.